Estudo da remoção de compostos orgânicos, benzeno e tolueno, em solução aquosa por processo oxidativo avançado do tipo Fenton - Evangelista, Zuzilene da Silva (2009)
The oil and petrochemical industry is responsable to generate a large amount of waste and wastewater. Among some efluents, is possible find the benzene, toluene, ethilbenze and isomers of xilenes compounds, known as BTEX. These compounds are very volatily, toxic for environment and potencially cancerigenous in man. Oxidative advanced processes, OAP, are unconventional waste treatment, wich may be apply on treatment and remotion this compounds. Fenton is a type of OAPs, wich uses the Fenton s reactant, hydrogen peroxide and ferrous salt, to promove the organic degradation. While the Photo-Fenton type uses the Fenton s reactant plus UV radiation (ultraviolet). These two types of OAP, according to literature, may be apply on BTEX complex system. This project consists on the consideration of the utilization of technologies Fenton and Photo-Fenton in aqueous solution in concentration of 100 ppm of BTEX, each, on simulation of condition near of petrochemical effluents. Different reactors were used for each type of OAP. For the analyticals results of amount of remotion were used the SPME technique (solid phase microextraction) for extraction in gaseous phase of these analytes and the gas chromatography/mass espectrometry The arrangement mechanical of Photo-Fenton system has been shown big loss by volatilization of these compounds. The Fenton system has been shown capable of degradate benzene and toluene compounds, with massic percentage of remotion near the 99%.